Handbook of Exoplanets 2017
DOI: 10.1007/978-3-319-30648-3_66-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Interior Structure of Terrestrial Exoplanets with Implications for Habitability

Abstract: Astrophysical observations reveal a large diversity of radii and masses of exoplanets. It is important to characterize the interiors of exoplanets to understand planetary diversity and further determine how unique, or not, Earth is. Assessing interior structure is challenging because there are few data and large uncertainties. Thus, for a given exoplanet, a range of interior structure models can satisfy available data. Typically, interior models aim to constrain the radial structure and composition of the core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…The predicted atmospheric compositions of rocky exoplanets based on geological properties, such as mantle f O 2 and initial volatile content, can in principle be compared to observations to test planetary formation and evolution scenarios. While properties such as the size and interior structure of a planet can already be observed, or may be inferred using mass radius observations (e.g., Dorn et al., 2017), establishing the mantle f O 2 or the bulk silicate H/C ratio will require observations of atmospheric chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted atmospheric compositions of rocky exoplanets based on geological properties, such as mantle f O 2 and initial volatile content, can in principle be compared to observations to test planetary formation and evolution scenarios. While properties such as the size and interior structure of a planet can already be observed, or may be inferred using mass radius observations (e.g., Dorn et al., 2017), establishing the mantle f O 2 or the bulk silicate H/C ratio will require observations of atmospheric chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we have yet to explore a larger parameter space, e.g. in mass and radius, but have only benchmarked our analysis with an Earth-sized planet, which would otherwise have an impact on the interior modeling (Unterborn et al 2016;Dorn et al 2018;. We nonetheless envisage that such an analysis is readily replicable with different parameter settings and is informative as presented to enable such an extension.…”
Section: Discussionmentioning
confidence: 99%
“…The former is also modeled to be relatively enriched in graphite/diamond (this should hold still even if some portion of native carbon species has been segregated into the core; Dasgupta et al 2013;Li & Fei 2014;Fichtner et al 2021), as shown in Table 4. Taken together, these factors preferentially impose a stagnant-lid tectonic regime (Hakim et al 2019;Dorn et al 2018;Noack et al 2017;Unterborn et al 2014).…”
Section: A Venus-like Geodynamic Regime?mentioning
confidence: 99%
“…In the literature, these are referred to as water worlds or ocean planets. However, irradiated water-rich rocky planets might also possess endogenic thick H 2 O-dominated, steam atmospheres, in which up to 100% of the planetary water content appears in vaporized form (Dorn et al 2018;Zeng et al 2019;Turbet et al 2020;Mousis et al 2020). If interactions between the (initially primordial, H 2 -dominated) atmosphere and magma oceans at the surface are considered, then close-in sub-Neptunes could have atmospheres with variable degrees of (exogenic) hydrogen and (endogenic) water (Kite et al 2020).…”
Section: Introductionmentioning
confidence: 99%